2018
DOI: 10.3390/md17010004
|View full text |Cite
|
Sign up to set email alerts
|

Two New Succinimide Derivatives Cladosporitins A and B from the Mangrove-derived Fungus Cladosporium sp. HNWSW-1

Abstract: Two new succinimide-containing derivatives, cladosporitins A (1) and B (2), were isolated from the fermentation cultures of the mangrove-derived fungus Cladosporium sp. HNWSW-1, along with a new pyrone, clapone (3), as well as the previously reported talaroconvolutin A (4) and anthraquinone (5). The structures of the isolated compounds were elucidated by 1D, 2D NMR, and HRMS spectral analysis. Compound 2 showed cytotoxicity against BEL-7042, K562 and SGC-7901 cell lines with IC50 values of 29.4 ± 0.35 μM, 25.6… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
35
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(35 citation statements)
references
References 28 publications
0
35
0
Order By: Relevance
“…Recently, a chemical analysis of the culture broth of the mangrove-derived fungus Cladosporium sp. HNWSW-1 resulted in the discovery of two new succinimide-containing derivatives, cladosporitins A and B (63 and 64), together with talaroconvolutin A (65) [60]. Compound 64 showed moderate cytotoxicity against three HTCLs, with IC 50 values from 25.6 to 41.7 µM, whereas 65 exhibited moderate cytotoxicity towards two HTCLs (IC 50 = 14.9 and 26.7 µM), as well as significant inhibitory activity against α-glycosidase (IC 50 = 78.2 µM) [60].…”
Section: -Decalinoyltetramic Acidsmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, a chemical analysis of the culture broth of the mangrove-derived fungus Cladosporium sp. HNWSW-1 resulted in the discovery of two new succinimide-containing derivatives, cladosporitins A and B (63 and 64), together with talaroconvolutin A (65) [60]. Compound 64 showed moderate cytotoxicity against three HTCLs, with IC 50 values from 25.6 to 41.7 µM, whereas 65 exhibited moderate cytotoxicity towards two HTCLs (IC 50 = 14.9 and 26.7 µM), as well as significant inhibitory activity against α-glycosidase (IC 50 = 78.2 µM) [60].…”
Section: -Decalinoyltetramic Acidsmentioning
confidence: 99%
“…Among them, compounds 90-92 are diastereomers of 103 [93], which was first reported in a patent as being able to induce differentiation of leukemic cells, as well as to have antibacterial and antifungal activities [81,96]. Cytotoxicity experiments revealed that cephalimysins 89-100 (except for 90) and 103, have moderate cytotoxic activity against several HTCLs [92,93,95], particularly 89, which is cytotoxic against the murine P388 and human HL- 60 [97].…”
Section: -Spirotetramic Acidsmentioning
confidence: 99%
“…Many isolated metabolites were aromatic compounds, i.e., phenalenones (190)(191)(192)(193)(194)(195)(196)(197)(198), grisane metabolites (199)(200)(201), and azaphilones . Linear polyketides with various side chains and other polyketides (246)(247)(248)(249)(250)(251)(252)(253)(254)(255)(256)(257) were also obtained.…”
Section: Other Polyketidesmentioning
confidence: 99%
“…A thermophilic micromycete of the Penicillium genus [73] was isolated from hot springs in Saudi Arabia using bioactivity-based separation of a culture liquid extract, from which a new polyketide was obtained (246).…”
Section: Other Polyketidesmentioning
confidence: 99%
See 1 more Smart Citation